Incidental English Vocabulary Learning Through TikTok A Conceptual Analysis - Sely, Garcia Raynando Aditya; Priyatmojo, Arif Suryo (Universitas Pahlawan Tuanku Tambusai, 2026)
The widespread use of social media has reshaped English learners’ exposure to vocabulary beyond formal classroom settings. Nevertheless, research on TikTok in English language education has largely emphasized its intentional pedagogical use, leaving the role of non-educational content in incidental vocabulary learning underexplored. This study aims to conceptually examine TikTok as an informal digital environment that supports incidental English vocabulary learning among EFL learners. Adopting a conceptual research design, the study synthesizes theories of incidental vocabulary learning, informal language exposure, and recent scholarship on digital media in ELT. The analysis indicates that non-educational TikTok content, code-switching practices, and interactive comment sections provide meaningful, repeated, and socially mediated vocabulary exposure. These characteristics position TikTok as an informal digital learning ecology where vocabulary acquisition emerges unintentionally through everyday digital engagement. The study concludes that TikTok can complement formal instruction by extending vocabulary learning opportunities beyond classroom boundaries.